MORPHOLOGICAL CHANGES OF RENAL STAGHORN NEPHROLITHIASIS. - M. I. Kogan; A. V. Hasigov; D. G. Pasechnik; I. I. Belousov (Вестник урологии)
Morphological changes in the kidneys of patients with staghorn nephrolithiasis at the time of endoscopic surgery staghorn calculi. In all cases, the morphological study of biopsy specimens revealed varying degrees of renal parenchyma lesions that may be predictors of chronic renal failure in patients with staghorn nephrolithiasis. Assessment of the extent of damage of the renal parenchyma is necessary for the timely implementation of renoprotective therapy.